2011
DOI: 10.1007/s10236-011-0421-8
|View full text |Cite
|
Sign up to set email alerts
|

Vertical dynamics of summer phytoplankton in a stratified estuary (Gulf of Finland, Baltic Sea)

Abstract: We present the results of multiparametric observations designed to follow the phytoplankton dynamics and interrelated physical, chemical and biological processes in the Gulf of Finland (Baltic Sea). Data were acquired by an autonomous moored water column profiler, an acoustic Doppler current profiler, a flow-through system installed aboard a ferry and by profiling and discrete water sampling aboard research vessels in July and August 2009. The main aim of the study was to investigate the processes responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Another example is from the Gulf of Finland, where less saline waters originating from the large rivers lying in the eastern part of the gulf usually spread along the northern coast. These less saline waters can occasionally detach from the coast and move for several months near the central axis of the gulf (Lips et al 2011), as observed recently.…”
Section: Surface Circulation and Related Processes-recent Findingssupporting
confidence: 65%
See 1 more Smart Citation
“…Another example is from the Gulf of Finland, where less saline waters originating from the large rivers lying in the eastern part of the gulf usually spread along the northern coast. These less saline waters can occasionally detach from the coast and move for several months near the central axis of the gulf (Lips et al 2011), as observed recently.…”
Section: Surface Circulation and Related Processes-recent Findingssupporting
confidence: 65%
“…On the basis of monitoring data for the period 1965-2000, Laine et al (2007) found a continuous decrease in salinity and density stratification until the early 1990s, after which there was a slight increase. Based on independent data for 1987-2008, Liblik and Lips (2011 found that the deep salinities in summer increased after the 1993 major inflow by about 2 g kg −1 . Despite the increased mean stratification strength and more frequent occurrence of hypoxia events (see Chap.…”
Section: 3mentioning
confidence: 99%
“…Nutrients below the thermocline can also be reached by motile phytoplankton, which migrate actively into the nutrient-rich waters below the thermocline (e.g. Olli 1999;Hajdu et al 2007;Lips et al 2011). Furthermore, it has been suggested that an early start to N fixation already in late spring may counteract N limitation during the decline phase of the spring bloom (Schneider et al 2003(Schneider et al , 2006.…”
Section: Carbon Inputsmentioning
confidence: 99%
“…According to one hypothesis, nutrient transport through the thermocline takes place as a result of the vertical migration (VM) of autotrophic organisms. This hypothesis is founded on the fact that there are phytoplankton species in the Baltic (mainly dinoflagellates like Peridiniella catenata, Scrippsiella hangoei and Heterocapsa triquetra) that are capable of undertaking vertical migrations (Lips and Lips, 2014;Lips et al, 2011;Olli, 2004;Olli et al, 1997). Moreover, dinoflagellates have been found capable of assimilating nutrients in the dark (Cullen, 1985;Cullen and Horrigan, 1981;Gisselson et al, 2002).…”
Section: Introductionmentioning
confidence: 96%